On Global Ionospheric Maps based winter-time GPS ionospheric delay with reference to the Klobuchar model : case study of the Northern Adriatic - Brčić, David (Array, 2019)
Modelling of the ionospheric Total Electron Content (TEC) represents a challenging and demanding task in Global Navigation Satellite Systems (GNSS) positioning performance. In terms of satellite Positioning, Navigation and Timing (PNT), TEC represents a significant cause of the satellite signal ionospheric delay. There are several approaches to TEC estimation. The Standard (Klobuchar) ionospheric delay correction model is the most common model for Global Positioning System (GPS) single-frequency (L1) receivers. The development of International GNSS Service (IGS) Global Ionospheric Maps (GIM) has enabled the insight into global TEC dynamics. GIM analyses in the Northern Adriatic area have shown that, under specific conditions, local ionospheric delay patterns differ from the one defined in the Klobuchar model. This has been the motivation for the presented research, with the aim to develop a rudimentary model of the TEC estimation, with emphasis on areas where ground truth data are not available. The local pattern of the ionospheric delay has been modelled with wave functions based on the similarity of waveforms, considering diurnal differences in TEC behavior from defined TEC patterns. The model represents a spatiotemporal winter-time ionospheric delay correction with the Klobuchar model as a basis. The evaluation results have shown accurate approximation of the local pattern of the ionospheric delay. The model was verified in the same seasonal period in 2007, revealing it successfulness under pre-defined conditions. The presented approach represents a basis for the further work on the local ionospheric delay modelling, considering local ionospheric and space weather conditions, thus improving the satellite positioning performance for single-frequency GNSS receivers.